Blood pressure in adults and its association with selected anthropometric and biochemical parameters - Rao, Katta Subraya Prakash; Mahesh, Saladi; C., Ramachandra Bhat (International Journal of Advances in Medicine, 2018)
Background: Hypertension is one of the known cardiovascular risk factors. Several epidemiological studies have found an association between various anthropometric indicators and hypertension. The present study was conducted to investigate the relationship between different commonly and uncommonly used anthropometric parameters, various biochemical parameters and hypertension in adults. Methods: A hospital based cross sectional study conducted among 300 adults aged 40 years and more, attending Medicine OPD of a tertiary care institution after obtaining their consent and permission from institutional ethical committee. Anthropometric measurements, blood pressure examination and relevant laboratory investigations were done. Results: Hypertension was seen in both obese and non-obese study subjects. BMI, waist circumference, neck circumference, sagittal abdominal diameter and CRP was higher in hypertensive males than normotensives and it was statistically significant. BMI, waist circumference, hip circumference, neck circumference, sagittal abdominal diameter and CRP had a positive correlation with systolic and diastolic blood pressure and it was found to be statistically significant. Conclusions: CRP, serum ferritin, sagittal abdominal diameter, hip circumference, waist circumference and neck circumference showed a positive correlation with both systolic and diastolic blood pressure, which means that WC and SAD can be used to get information about visceral obesity in an individual. This also suggests that decrease in intra-abdominal fat could decrease the blood pressure.